Modeling an aggregate production planning - Zanella, Fernando (2022)
This paper aims to present and discuss the benefits that small- and medium-sized companies can get when using mathematical programming to help in the decision-making process regarding aggregate production planning. The aggregate plan is concerned with determining the quantity of a good or a family of goods to be produced and also scheduling its production for the medium-range period, in which the main objective is to meet forecast demand while minimizing costs. To exemplify an aggregate production planning problem, a simplified model of a real company, considering four months, was proposed. Future developments should improve the model to consider other data such as inventory management and costs; raw material storage and logistics; employee costs, contracting and subcontracting and overtime.